Pengaruh Diversifikasi Pendapatan, Risiko Kredit, dan Efisiensi terhadap Profitabilitas dengan Ukuran Bank sebagai Variabel Moderasi: Studi Empiris pada Perbankan di Indonesia - Listin Afriani; Fatimah Fatimah; Mister Candera (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to analyze the effect of revenue diversification, credit risk, and efficiency on bank profitability and examine the role of bank size as a moderating variable. Using an associative research method with a quantitative approach, the study population included 46 banking companies listed on the Indonesia Stock Exchange (IDX) for 2020–2024. Using purposive sampling, the study selected 15 banks, yielding 75 observations. The study analyzed secondary data using descriptive statistics, classical assumption tests, and moderated regression analysis (MRA). Profitability was measured using return on assets (ROA), revenue diversification using the net interest income (NII) ratio, credit risk using non-performing loans (NPL), and efficiency using the operating expense (BOPO) ratio. The results showed that revenue diversification and efficiency significantly negatively impacted profitability, while credit risk significantly positively impacted profitability. Furthermore, bank size strengthened the effect of revenue diversification on profitability and weakened the effect of credit risk on profitability. However, bank size did not significantly moderate the effect of efficiency on profitability.